Digitalization and Integration of e-KTP and the Indigenous People It Left Behind - Effendy, Edrick Edwardina; Gifta, Elmira (Sekolah Tinggi Ilmu Kepolisian, 2025)
This article aims to highlight the discrepancies between the regulation and the implementation of laws regarding identities and the administration of the indigenous communities in Indonesia, and how these issues occur and persist. Indonesian Identity Card or KTP and its electronic variant, e-KTP, is considered the primary identifying means for Indonesian citizenship, with the Population Administration Act (Law No. 23/2006, later amended by Law No. 24/2013) even mandating the government to provide all public services based on the NIK or Customs Identification Number. Consequently, this poses a risk of excluding and marginalizing certain segments of the population, namely the Indigenous people of Indonesia, as this document has become mandatory for accessing essential services provided by the government. This exclusion and discrimination of indigenous groups and communities is based on a lack of access to register for the e-KTP itself, and is even based on religion and identity. To examine this issue, this article uses qualitative research, specifically grounded theory methodology, by examining data and law, and reviewing reports made by or of a few different Indigenous communities throughout Indonesia– namely, case studies and reports from indigenous communities in Banten, Sumatra, and Papua, to get a better understanding of this nationwide issue. This article elucidates systemic issues that occur and the problems that emerge from relying solely on one specific identification document for Indigenous people and communities in Indonesia.